Upaya Mencegah Pelanggaran Praktik Monopoli Yang Dilakukan Oleh PT. Angkasa Pura - Ovilia Shely Fadhila (Lex Renaissance, 2020)
This study discusses two legal questions: first, why the airport administration carried out by PT Angkasa Pura (Persero) violates Article 50 letter a and Article 51 of Law No. 5 of 1999 on the Prohibition of Monopoly and Unfair Business Competition? Second, how are the arrangements for the implementation of airport business activities in accordance with the competition law? The research method used is normative juridical. The results of the study conclude, first, the airport administration carried out by PT Angkasa Pura I (Persero) and PT Angkasa Pura II (Persero) as BUMN based on the 3 Decisions of the Business Competition Supervisory Commission (KPPU) violates the prohibition of monopolistic practices due to inconsistency in the behavior of business actors in carrying out business activity contract that they carry out monopolistic practices beyond the rules stipulated in the provisions of the laws and regulations. Second, the government can refer to the OECD Regulatory Impact Assessment Toolkit, which is a systemic approach to critically assess the positive and negative effects of regulation and non-regulatory alternatives related to airport administration. In addition, it is also very necessary to improve the regulations for airport business governance which are still centralistic and monopolistic in nuances.